Development of biomimetic sensor for fast and sensitive detection of Norfloxacin - Gobatto, Daniel Ferreira [UNESP]; Wong, Ademar [UNESP]; Lanza, Marcos Roberto de Vasconcelos [UNESP]; Sotomayor, Maria Del Pilar Taboada [UNESP] (Bentham Science Publishers, 2010)
A biomimetic sensor is proposed as a promising new analytical method for determination of norfloxacin (NF) in pharmaceuticals. The sensor was prepared by modifying a glassy carbon electrode surface with a Nafion® membrane doped with poly(copper phthalocyanine) complex [poly-CuPc]. Amperometric measurements carried out with the sensor under an applied potential of -0.05 V vs Ag|AgCl in 0.1 mol L-1 acetic acid containing 1.5 × 10-3 mol L-1 hydrogen peroxide showed a linear response range from 2.0 × 10-4 to 1.2 × 10-3 mol L-1. Selectivity and interference studies were also performed. A sensor response mechanism is proposed, based on the experimental evidence. Recovery studies were carried out using environmental samples, in order to evaluate the sensor’s potential for use with these sample classes. Finally, sensor performance was evaluated using analyses of commercial formulations.
Keywords: Norfloxacin; Fluoroquinolones; Biomimetic sensors; Poly(copper phthalocyanine)